Work conditions and their repercussions on the quality of life of rural workers* - Oliveira, Jeane Cristina Anschau Xavier de; Corrêa, Áurea Christina de Paula; Cezar-Vaz, Marta Regina; Marcon, Samira Reschetti; Rosa, Isabele Torquato Mozer; Dalprá, Luanna Arruda e Silva (Revista da Escola de Enfermagem da USP, 2021)
Objective: To assess the context of work and analyze their repercussions on the quality of life of rural workers in soybean agribusiness. Method: Cross-sectional study, with an intentional sample of rural workers, conducted between the months of October and December 2019, with the application of the instruments World Health Organization Quality Life-bref and Scales of Assessment of Context and Human Cost of Work. The data were analyzed through bivariate and multivariate descriptive statistics. Results: The participants amounted to 299 rural workers. The scores of Work Conditions and Socioprofessional Relations were satisfactory and Organization of Work was critical. The scores of Physical and Cognitive costs were considered critical and of the Affective Cost was satisfactory. The Socioprofessional Relations have negatively impacted the overall quality of life and the Physical and Psychological, the Social Relations and the Environmental Domains, whereas Cognitive Cost positively impacted the Physical and the Environmental Domain and the Affective Cost positively impacted the Social Relations Domain. Conclusion: Although the Work Context and Human Cost indicated adverse conditions, only the Socioprofessional Relations exerted negative influences on the quality of life of rural workers.